Hubungan Pendidikan Spiritual Dengan Tingkat Kedisiplinan Siswa - Melani Melani; Bahtiar Siregar; Januari Simarmata; M. Randi Al Farizi; Karmila Astuti; Trisnawati Lubis (Journal on Education, 2024)
Spiritual education is rooted in the belief that educational activities are a form of worship to Allah (God). Discipline is a gradual process of training the minds and characters of children, enabling them to develop self-control and contribute positively to society. In this era of globalization, there has been a crisis in discipline and a decline in the morals of students.This research aims to investigate the relationship between spiritual education and the level of student discipline in schools. The study adopts a qualitative approach, focusing on the method of literature review or library research.Based on the literature review, it is found that there is a positive correlation between students' spiritual education and their level of discipline in school. Initiatives from schools, particularly educators, are necessary not only to enhance discipline but also to elevate the students' spirituality through engaging spiritual education.